ROS-mediated endoplasmic reticulum stress and mitochondrial dysfunction underlie apoptosis induced by resveratrol and arsenic trioxide in A549 cells. (5th February 2016) - Gu, Shiyan; Chen, Chengzhi; Jiang, Xuejun; Zhang, Zunzhen
Abstract: Although it is well documented that endoplasmic reticulum (ER) stress and mitochondrial dysfunction are associated with apoptosis, little is known about whether they are involved in the apoptotic cell death induced by resveratrol and arsenic trioxide (ATO) combination. In this study, we identified a series of sensitization effects of resveratrol on human lung adenocarcinoma A549 cells to ATO treatment, with the combination index (CI) of resveratrol and ATO less than 1. Then, we demonstrated that ER stress was contributed to this synergistic effect, which was manifested by increased the expression levels of ER stress hallmarks, including 78-kDa glucose-regulated protein (GRP 78), caspase 12 and C/EBP-homologous protein (CHOP), In addition, mitochondrial dysfunction was observed after exposure of A549 cells to resveratrol or/and ATO, which was displayed by some alterations of mitochondria-related events, such as loss of mitochondrial membrane potential, cytochrome c release and changes of Bax and Bcl-2 expressions. Our results further demonstrated that resveratrol and ATO-induced ER stress and mitochondrial dysfunction were mediated by reactive oxygen species (ROS), showing that pre-treatment of N-acetyl-l -cysteine, a potent ROS scavenger, restored the ER stress and mitochondrial dysfunction in cells co-treated with resveratrol and ATO, thereby leading to the reduction of the apoptosis. Collectively, these results clearly suggest that ROS-mediated ER stress and mitochondrial dysfunction were involved in the apoptosis induced by resveratrol and ATO in A549 cells, which provides a novel insight into the molecular mechanisms of resveratrol-mediated ATO-sensitization. Highlights: Resveratrol synergistically sensitizes ATO in A549 cells. ER stress plays a critical role in resveratrol and ATO-triggered apoptosis. ER stress and mitochondrial dysfunction are regulated by ROS.